Lecturer’s Perception on the Integration of 21st Century Learning Skills in the Teaching of English Prose - Hasbi, Muhammad; Mahmud, Murni; Halim, Abdul (ELT Worldwide: Journal of English Language Teaching, 2023)
This study aims at investigating lecturer’s perception on the integration of 21st century learning skills or 4Cs in the teaching of English prose. This research employed a descriptive qualitative research design with a single case study approach. A semi-structured in-depth interview was used to obtain data from the subject of the research and the data was analyzed by using Braun and Clarke’s six steps thematic analysis. The result of the research shows that (a) the lecturer has a positive perception on the integration of the 4Cs in the teaching of English prose; (b) the lecturer has a good perception and understanding on the content of the 4Cs; and (c) the lecturer also has good perception on the implementation of the 4Cs in the teaching of English prose by identifying four key elements related to the integration of the 4Cs in the teaching of English prose. The expressed perception aligns with the implementation of 4Cs in the teaching of English prose, where the lecturer strives to design English prose learning activities that are tailored to the elements of 4Cs to ensure that the target of improving students' 4Cs skills can be achieved. The present study implies the positive evaluation and comprehension of the lecturer, combined with the recognition of essential components for application, underline the prospect of expanding the quality of English composition education.